The Impact of Social Media Marketing Strategies on Consumers’ Purchase Intention: Evidence from Instagram-Based Marketing - Suraidah Sarbia (Vifada Management and Social Sciences, 2024)
This study aims to examine the influence of social media engagement dimensions openness, participation, conversation, community, and connectedness on purchase intention on Instagram. A quantitative research approach was employed to provide empirical evidence on how interactive marketing features shape consumer behavior in social commerce environments. Data were collected using a structured questionnaire consisting of 20 measurement items distributed via Google Forms to 100 respondents who had previously made purchases through social media platforms. The data were analyzed using statistical techniques to assess the significance and direction of the relationships between variables. The findings indicate that openness has a positive and significant effect on purchase intention, suggesting that transparent information sharing increases consumer trust. Participation also shows a positive and significant influence, highlighting the importance of user involvement in content creation and engagement. Furthermore, conversation significantly enhances purchase intention, emphasizing the role of interactive communication between brands and consumers. The community variable demonstrates a positive and significant effect, indicating that a strong sense of belonging within online brand communities encourages buying interest. Lastly, connectedness positively and significantly affects purchase intention, reflecting the value of social ties and network integration on Instagram. Overall, this study confirms that social media engagement dimensions play a critical role in driving consumer purchase intention and provides practical implications for digital marketing strategies focused on interactive and community-driven approaches on Instagram.